Ram semen quality can be assessed by flow cytometry several hours after post-fixation. Issue 2 (13th April 2021) - Vašíček, Jaromír; Svoradová, Andrea; Baláži, Andrej; Jurčík, Rastislav; Macháč, Marián; Chrenek, Peter
Summary: Ram spermatozoa are very sensitive to any cold shock or oxidative damage, therefore making them unsuitable for prolonged storage or distant transport to specialized laboratories for flow-cytometric analysis. The aim of this study was to stain ram semen samples with several fluorescent markers and analyse their stability during formaldehyde fixation. Briefly, freshly collected semen samples were stained for apoptosis (annexin V-FITC, YO-PRO™-1 and FLICA), acrosomal damage (PNA-AF488 and FITC-conjugated antibody against GAPDHS), mitochondrial activity (Mitotracker probes), oxidative damage [dihydroethidium (DHE) and CellROX™ Green] and cell viability (live/dead fixable viability dyes). Next, samples were fixed in buffer containing formaldehyde and then washed. Stained sample were analyzed using flow cytometer before fixation, immediately after fixation, and at 5 h and 20 h post-fixation. Fluorescent signals and the proportion of positively stained spermatozoa were compared statistically in fresh and post-fixed samples. All examined markers, except YO-PRO-1 (decreased significantly, P < 0.05), retained their fluorescence intensities after fixation. In conclusion, several tested markers were able to withstand formaldehyde fixation of ram semen samples as follows: annexin V and FLICA for apoptosis; PNA for acrosomal status; MitoTracker Red CMXRos for mitochondrial activity; and CellROX Green for oxidative status in combination with a suitable live/dead fixable viability dye. This optimized methodology could help to comprehensively analyse the quality of ram semen from local farms countrywide.